MEASURING AND ANALYZING THE IMPACT OF MONETARY POLICY TOOLS IN CONTROLLING INFLATION RATES IN IRAQ FOR THE PERIOD 2004-2022 - Khalil Ismail Aziz; Hamad Mahmood (Galaxy International Interdisciplinary Research Journal, 2024)
The study aimed to show the extent of the ability of monetary policy to use its tools and the nature of its work in controlling inflation rates in the Iraqi economy for the period (2004-2022), , through the use of the analytical and standard method, and the study showed in the descriptive aspect the relationship between the tools used for monetary policy and the phenomenon of inflation, cash. The results of estimating the relationship in the standard side using the methodology of the self-regression model for distributed slowdown (ARDL) showed that there is a statistically significant relationship between monetary policy and inflation, and the results showed that the Central Bank of Iraq was able through the use of monetary policy tools to reduce an important percentage of inflation rates despite the economic and security conditions that the country is going through.